Management of Islamic Religious Education In Developing The Noble Ability of Santries Through The Tahfidz Approach - Rohaeti Rohaeti; Ulfiah Ulfiah; Daeng Arifin; Ahmad Khori (Syntax Corporation Indonesia, 2021)
The purpose of national education in Law Number 20 of 2003 concerning the National Education System chapter II article 3 emphasizes the aspect of faith and devotion, the second aspect is noble character. However, the practice of education in Indonesia is still not in accordance with the functions and objectives of national education. Pesantren is an appropriate model of education in fostering noble character because students are fully trained and accustomed to filling their sight, hearing and heart with content that is beneficial for their lives. The tahfidz approach is the right approach in fostering noble character because the series of processes in tahfidz activities are able to bring students closer to the Qur'an and Allah. The problem of students' morals is caused by several things including an inappropriate approach, an atmosphere or culture that is not yet supportive, teacher competence, and the lack of adequate human resources for tahfidz teachers. The approach used in this study is a qualitative interactive mode of inquiry approach. The method used is descriptive analytical method with a variety of case studies. While the data collection techniques are observation/observation, participation, interviews, and literature study. The conclusion is that the Pesantren Leader and the team that was formed made a context analysis document as a study in planning. The planning of Islamic religious education in order to foster noble character in the two Islamic boarding schools, namely the Tahfidz Misbahunnur Islamic Boarding School in Cimahi City and the Darul Arqom Muhammadiyah Islamic Boarding School in Garut Regency, is stated in the pesantren curriculum document. The implementation of Islamic religious education management is carried out through the tahfidz approach. The two pesantren set a number of indicators of the success of the Islamic religious education management process in fostering noble character through the tahfidz approach, namely: obedience to Allah and His Messenger, enthusiasm, tolerance, carefulness, thoroughness, compassion, patience and honesty.